(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Mutagenesis is one of the most effective methods for crop improvement as it expands the genetic pool, offering more opportunities for selecting desirable traits, especially in cowpea, which is predominantly self-pollinating. For effective mass irradiation at acute doses, the sensitivity of cowpea genotypes to gamma rays needs to be determined. The objective of this study was to determine the lethal dose (LD50) at 50% germination and reduction in the appearance of cowpea growth (RD50) when exposed to gamma radiation. Five cowpea genotypes, namely, Hansadua, WC-36, ACC122WxWC-10, IT97K-819, and WC-10, were irradiated with gamma radiation from a 60Co radioactive source at 0-1200Gy with an interval of 100 Gy. The results showed significant wide variations in the responses of genotypes. Hansadua, an improved cultivar, had the lowest LD50 and RD50 values of 531.0 and 452.0 Gy, respectively, indicating its high sensitivity to gamma radiation. Thus, suggesting a relatively lower dose is required to kill half of the population and more so, a tendency to produce more useful mutants at lower doses of radiation from which selection could be made. In addition, the highest values of LD50 and RD50 were observed for ACC122WxWC-10 at 903.0 and 694.0 Gy, respectively. This implies that the ACC122WxWC-10 genotype was the least sensitive to gamma radiation, as more radiation was required to reduce the growth of the control population to half. In addition, there were progressive reductions in other parameters such as plant height, root length, shoot weight, and whole plant weight in all genotypes as the radiation dose increased. Int. J. Agril. Res. Innov. Tech. 15(1): 127-135, June 2025